Tari Kalih Garu sebagai Materi Latihan Motorik Kasar Siswa Sekolah Dasar Kelas Tinggi - Sakinah, Anissa Citra; Fitriani, Yulianti (Didaktika, 2021)
This research is a scientific development project which is motivated by the inexistence of Padepokan Pencak Silat or Sanggar in the community around the residents live located in Citra Gading RT 02 RW11 Serang City, Banten Province which can accommodate the creativities of upper class (grade IV-VI) of elementary school students. The aim of this research is to develop a combination dance adapted from tradisional martial arts of Indonesia, Pencak Silat. This research uses a developmental method or RD designed from Dick Carry by ADDIE model which has five stages, namely analysis, design, development, implementation, and evaluation. This dance uses eleven movements that have been adapted from Pencak Silat. The subjects in this study were 6 high-grade elementary school students. The research technique was carried out by means of observation, interviews, documentation, and a questionnaire. The results of this study were that there was an increase in students' gross motor scores from the first day of implementation to the third day of implementation. The children were more flexible and more dexterous in moving. Therefore, this dance can contribute to the development of gross motoric skills of high school students including aspects of speed, strength, endurance, and good agility that can be used by teachers, coaches and even parents at school and in environment where they live, even at pandemic times like this period.